Hypertriglyceridemia-induced Acute Pancreatitis in Pregnancy - Serpytis, Mindaugas; Karosas, Vytautas; Tamosauskas, Rokas; Dementaviciene, Jurate; Strupas, Kestutis; Sileikis, Audrius; Sipylaite, Jurate (JOP. Journal of the Pancreas, 2012)
Context Hypertriglyceridemia is a well known phenomenon of pregnancy occuring due to physiologic changes in sex hormone levels. Occasionally, it could lead to development of acute pancreatitis. Gestational hypertriglyceridemia-induced acute pancreatitis occurs in pregnant women usually with preexisting abnormalities of the lipid metabolism and is associated with additional diagnostic and therapeutic challenges related to hypertriglyceridemia and pregnancy. Case report We present a case of the hypertriglyceridemia-induced acute pancreatitis in pregnant woman with no previous history of lipid abnormality and pregnancy as the only known triggering factor for hypertriglyceridemia. Conclusions Hypertriglyceridemia-induced acute pancreatitis is a rare complication of pregnancy; however, it should be suspected in all pregnant patients admitted for nonobsteric abdominal pain. Image: CT image showing a diffusely enhancing and enlarged pancreas with hypodense foci in the pancreatic head.